ПОАСПЕКТНЫЙ И КОНТЕНТ-АНАЛИЗ В ИЗУЧЕНИИ ЧИТАТЕЛЬСКОГО РАЗВИТИЯ (НА МАТЕРИАЛАХ ЖУРНАЛА «READING RESEARCH QUARTERLY» ЗА 2004-2007 гг.) (Библиосфера)
The application of methods of publications aspect by aspect- and content analysis to study of the problems and tendencies in the investigations of a reader's personality are described.